Response of orange seedlings to the proportion of nitrate-ammonium in the nutrient solution and the benefits of phosphorus in ammonia toxicity - Moda, Leandro Rosatto [UNESP]; de Mello Prado, Renato [UNESP]; Souza Júnior, Jonas Pereira de [UNESP]; da Silva Júnior, Gabriel Barbosa; dos Santos, Luiz Cláudio Nascimento [UNESP]; Soares, Marcus Vinicius Gomes [UNESP]; Kadyampakeni, Davie Mayeso (Elsevier, 2021)
The imbalance between nitrate/ammonium (NO3−/NH4+) ratio in the nutrient solution induces ammonia toxicity that can be attenuated by phosphorus (P). However, there are no reports of the beneficial effect of P in mitigating ammonia toxicity for citrus. The aim of this study was to evaluate the response of orange seedlings to nitrogen (N) in different NO3−/NH4+ ratios in the nutrient solution and whether P attenuates ammonia toxicity. Thus, two experiments were conducted in a greenhouse. Experiment I consisted of five NO3−/NH4+ ratios, and experiment II of three concentrations of P supply combined with two NO3−/NH4+ ratios. About 120 days after the beginning of the treatment applications, biological and nutritional evaluations were carried out in both experiments. The best NO3−/NH4+ ratio was 80/20 for promoting the greater development of orange seedlings Pêra-rio (Citrus sinensis L.) grafted on lemon tree (Citrus limonia L.). On the other hand a NH4–N:NO3–N ratio of 26:74 induces severe ammonia toxicity in the plant. Increasing the concentration of P supply in the nutrient solution (10.0 mmol L−1) is an important new strategy to mitigate ammoniacal toxicity in these plants because it reduced the leakage of electrolytes and increased the production of photosynthetic pigments, the photosynthetic rate, the dry matter production and the seedling quality.
Keywords: Ammonia toxicity; Citrus sinensis L. Pêra-rio; Nitrogen form; Phosphorus; Plant growth